Isolation and characterization of biofilm degrading bacteriophage from Gulshan lake specific for escherichia coli and vibrio cholerae - Anika, Afroza Khanam (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.